Cinacalcet hydrochloride for the treatment of hyperparathyroidism - Verheyen, Nicolas; Pilz, Stefan; Eller, Kathrin; Kienreich, Katharina; Fahrleitner-Pammer, Astrid; Pieske, Burkert; Ritz, Eberhard; Tomaschitz, Andreas (Expert opinion on pharmacotherapy, 2013)
Introduction: Effective therapeutic strategies are warranted to reduce the burden of parathyroid hormone excess related morbidity and mortality. The calcimimetic agent cinacalcet hydrochloride is a promising treatment strategy in hyperparathyroidism. Areas covered: This review provides an overview of the pharmacokinetics, clinical efficacy, cost-effectiveness, safety and the efficacy profile of cinacalcet in the setting of primary and secondary hyperparathyroidism (p/sHPT). The authors searched PubMed database for English language articles related to cinacalcet in human subjects, published till Dec 2012 - focusing on the period between 2008 and 2012. Expert opinion: The use of cinacalcet in pHPT can be considered on those hypercalcemic patients in whom parathyroidectomy is not performed. However, data on the impact of cinacalcet on hard clinical outcomes in pHPT are missing. Despite effective improvements of biochemical parameters of sHPT, the intention-to-treat-based analysis of the EVOLVE trial did not support the notion that cinacalcet significantly reduces the risk of death or major cardiovascular events in dialysis patients with moderate-to-severe sHPT. Considering the strong evidence indicating beneficial effects of cinacalcet in the setting of HPT, further randomized controlled trials are definitely warranted to evaluate whether calcimimetic treatment might improve mortality and cardiovascular risk in patients with parathyroid hormone excess over a broad spectrum of kidney function.